ChemInform Abstract: All‐Inorganic Networks and Tetramer Based on Tin(II)‐Containing Polyoxometalates: Tuning Structural and Spectral Properties with Lone‐Pairs. Issue 2 (January 2015) - Zhao, Chongchao; Glass, Elliot N.; Chica, Bryant; Musaev, Djamaladdin G.; Sumliner, Jordan M.; Dyer, R. Brian; Lian, Tianquan; Hill, Craig L.
Abstract Structural and spectral features of Sn(II)‐containing polyoxometalate networks (IVa, b) and the molecular compound (VI) are investigated by XRD, Raman and UV/VIS spectroscopy, electrochemical measurements, and DFT calculations.